The Mustachioed Woman, or The Problem of Androgyny in Victoria Cross’ Six Chapters of a Man’s Life - Ana Raquel Rojas (Cahiers Victoriens et Edouardiens)
While Victoria Cross’ novel Six Chapters of a Man’s Life has now largely fallen into obscurity, it has a new relevance in terms of contemporary theories of performativity and gender identity. The novel focuses on the impossibility of seeing androgyny as a coherent gender identity; instead, androgyny is presented as fragmented and illegible. Cross first published an excerpt from this novel in the Decadent journal The Yellow Book, and titled the short-story “Theodora, a Fragment,” which has been reprinted in Elaine Showalter’s anthology Daughters of Decadence. Both the story and the novel focus on the problems of desiring the androgyne. The male narrator, Cecil, finds himself first attracted to and then frustrated by the ever-shifting gender identity of his female lover, Theodora, who secretly cross-dresses as a man, Theodore, so that they may travel together unmarried. Drawing on Judith Butler’s theories of gender and identity, this article explores how androgyny functions as a primary gender tempered by its opposite—either feminized masculinity or masculinized femininity—and the impossibility of seeing androgyny as a coherent identity outside this gender binary.